Hydrates Drilling Muds Rheological Properties - Lal, B. (Springer Nature, 2022)
This section discusses the drilling mud rheological properties data suitable for drilling hydrate sediment. Almost all the articles related to hydrate drilling mud for drilling hydrate sediment and hydrate management is drilling during deepsea drilling are discussed. The gathered data is tabulated for academic and field practical use. Drilling mud properties such as PV, AV, FL, and gel strength are the main focus of this section. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.